THE FLUID SYSTEMS FOR THE SLD CHERENKOV RING IMAGING DETECTOR - Abe, K.; Antilogus, P.; Aston, D.; Baird, K.; Bean, A.; Bendavid, R.; Bienz, T.; Bird, F.; Caldwell, D. O.; Cavallisforza, M.; Coller, J.; Coyle, P.; et al. (Institute of Electrical and Electronics Engineers (IEEE), 1993)
We describe the design and operation of the fluid delivery, monitor and control systems for the SLD barrel Cherenkov Ring Imaging Detector (CRID). The systems deliver drift gas (C2H6+TMAE), radiator gas (C5F12+N2) and radiator liquid (C6F14). MeasUred critical quantities such as electron lifetime in the drift gas and ultra-violet (UV) transparencies of the radiator fluids, together with the operational experience, are also reported.